SIDS; bed sharing and passive smoking, the leading causes in Pakistan- Letter to the Editor - Ajaz Ahmad; Tehreem Samee; Iqra Farooq (Journal of the Pakistan Medical Association, 2026)
Madam, Sudden infant death syndrome (SIDS) refers to the unexpected death of an otherwise healthy infant that remains unexplained even after a full autopsy. A negative history as well as a negative autopsy result is necessary for SIDS. Multiple factors have been consistently associated with increased risk, including prone sleeping position, maternal smoking, excessive bedding or clothing, elevated room temperature, and low socioeconomic status. Although the exact causes of SIDS are unknown, airway obstruction, rebreathing of expired gases, and heat-related stress are thought to be the main culprits. (1) In Pakistan, it is a common habit to share a bed with infants. According to studies, sharing a bed is one of the great risk factors leading to SIDS. Families from lower socioeconomic backgrounds, as well as some educated households, often consider bed-sharing to be safe. The risk is even more elevated if one of the parents is a smoker. According to research held at Aga Khan University, 95% of people suffer from secondhand smoking in Pakistan. In a cohort of 119 bed-sharing infant deaths, 88 deaths were due to SIDS, accidental suffocation accounted for 16, while 15 deaths remained undermined. In 29.4% of the cases, head or faces were covered by the bedding. (2) Upon comparison, it was seen that when compared to children of non-smoking parents, the risk of SIDS among the children of smoking parents increased threefold; The greater the number of cigarettes smoked per day, the higher the risk. (3) This letter aims to highlight the risks of bed-sharing. It is advised to share the room with the infant rather than the bed. The infant should be in a cot near the bed. If the parents are smokers, then it is advised not even to share the room. Despite being a leading cause of infant mortality globally, it is still under research in Pakistan. It is concerning that there is almost no data available on WHO related to infant deaths due to SIDS in Pakistan because most of the cases go unreported. There is a huge knowledge gap about SIDS due to bed sharing and passive smoking. Parents remain unaware of its risk due to the lack of awareness. Physicians should counsel the parents and researchers should play their role through publications.